The role of monkey inferior parietal cortex in visual discrimination of identity and orientation of shapes. - Eacott, M; Gaffan, D (1991)
Three cynomolgus monkeys (Macaca fascicularis) were tested for their visual learning ability following bilateral lesions to the inferior parietal cortex. In discrimination learning with patterns differing from each other in form and colour their performance was normal. In discriminating monochromatic patterns their performance depended on the nature of the pattern discrimination; when the discriminanda were different shapes (e.g. x,v) they performed well, while with discriminanda which differed only in the orientation of the shape (e.g. p,d) they performed relatively badly. These results were compared to the previously reported results of normal animals and animals with inferior temporal lesions performing the same task. The ratio of errors in orientation discrimination to errors in shape discrimination was significantly higher than normal in the group with parietal lesions, and significantly lower than normal in the group with inferior temporal lesions. These results suggest that the roles of inferior temporal and inferior parietal cortex in the discrimination of shape and orientation are complementary.